Ukraine refugees: From temporary protection to encouraging return to support the Ukrainian economy - Yuriy Gorodnichenko; Daniel Gros (EconPol Forum, 2025)
War of attrition. President Trump's promises of a quick end to the war are unlikely to come true. German and European policy must shift from providing temporary protection to supporting a productive return to support the Ukrainian economy. At present many Ukrainian refugees still require substantial financial support from their host country. This is particularly the case in Germany, with the fiscal cost sapping popular support for Ukraine. Ukraine needs people to strengthen its economy, including the ramping up of domestic production of weapons and machinery. A productive return thus yields a double dividend. German and European enterprises should be encouraged to start producing in Ukraine by providing them with a guarantee against bomb damage. European FDI in Ukraine, in particular by German SMEs, could provide returning refugees with productive jobs. Encouraging the productive return of refugees would also make sense in the unlikely event of a near-term cessation of hostilities.
Keywords: 330